Understanding and Preventing Cognitive Errors in Healthcare - Marjorie Stiegler; Sara Goldhaber-Fiebert (Association of American Medical Colleges, 2015)
Abstract Introduction Cognitive errors are errors made despite possessing adequate knowledge and skill to effectively make the right decisions, often due to subconscious influences. Medical emergencies require rapid decision making with high stakes outcomes, and as such, specific tools are needed to combat thinking errors that lead to diagnostic or therapeutic missteps. This resource was created as part of a recent focus in safety literature about diagnostic delay and misdiagnosis as a major sphere of medical error. Given this, this brief animated video, filmed at the Stanford University School of Medicine's Immersive Learning Center as a collaboration between Stanford and University of North Carolina Chapel Hill physicians, describes some introductory concepts about medical decision making errors and strategies to avoid them. Methods This resource contains a video that serves as a trigger for discussion. A supplemental PowerPoint presentation highlighting core principles, and a PDF exploring the topic of "Illness Scripts" are also provided. Results Trainees have given positive feedback about the content of this video, and clinicians of many different specialties and professions have given similarly positive feedback in the context of national workshops and other presentations of the content. Such learners consistently reported that the summarized techniques were among the most valuable take-home points from the day-long simulation course. In addition, learners consistently report that the video and animations make the material memorable and easily digestible, much more so than a lecture format or extensive reading of primary resources in the literature. In addition, one learner, a surgeon with a 40-year career, reported that he felt the process of understanding a mistake he had made years ago and carried with him as a burden for decades was cathartic and normalizing. The same is true for trainees. Discussion This video and subsequent discussion effectively define and illustrate the concept of cognitive error in healthcare decision making, and offer strategies to prevent, or recover, from such errors. We have found that encouraging participants to discuss prior mistakes they have made themselves or heard about others making during emergencies or critical cases normalizes and humanizes the experience of vulnerability to being wrong.